Technical skill differences in stroke propulsion between high level athletes in triathlon and top level swimmers - Bottoni, A.; Lanotte, N.; Boatto, P.; Bifaretti, S.; Bonifazi, M. (Journal of Human Sport & Exercise, 2011)
In the latest decades the arm propulsion mechanism in human swimming has been an issue of great interest for researchers. The availability of new devices which can easily measure the stroke propulsion by means of a non invasive gauge allows the study of technical skills in real swimming, without artificial and distorting conditions like in a swimming flume or in tethered swimming. Performance in swimming is a crucial factor in another sport such as Olympic Triathlon, however we saw that the triathlon athletes presented shortfalls and differences with respect to expert swimmer, particularly in mean pressure and resultant momentum, but not maximum pressure. Each athlete showed a distinctive shape of the pressure curve, but triathletes present a greater variability in the pressure pattern than competitive swimmers, as is the case of novice vs. expert swimmers observed in previous studies. The possibility of pointing out some differences in stroke propulsion between top level swimmers and high level athletes in triathlon could give some useful indications for coaches in planning triathlon training.